Impact of internal carotid endarterectomy on visual fields: a non-randomised prospective cohort study in Austria. Issue 10 (16th October 2017) - Konstantiniuk, Peter; Steinbrugger, Iris; Koter, Stephan; Muehlsteiner, Johanna; Wedrich, Andreas; Cohnert, Tina
Abstract : Purpose: The goal of this study was to determine whether internal carotid endarterectomy is associated with visual field changes. Methods: Between March 2007 and December 2010, a cohort study involved 29 patients with stenosis of the carotid artery. All patients underwent ophthalmoscopy and kinetic visual field examination (Goldmann perimetry) preoperatively and postoperatively. Furthermore, a detailed area calculation was performed. On both the operated and the contralateral side, the areas surrounded by the different isopters (isopter areas) were determined and preoperative and postoperative values compared. The three isopters were classified from the centre to the periphery (I, II and III). Isopter area values are given as ratio compared with total perimetric circle. p Values <0.05 were considered to be statistically significant. Results: 1) The ophthalmologists assessment Eight of eleven patients with precarotid endarterectomy impairments experienced focal or concentric improvement. Six cases with preoperative concentric narrowing of the isopters returned to normal or improved substantially. Three out of 18 patients with normal preoperative visual field presented with deteriorations after surgery, two cases with ipsilateral and one with contralateral focal impairment. In 15 cases, there was no preoperative or postoperative abnormality. 2) Area calculation (preoperative area, postoperative area, P) Ipsilateral: isopter area I (0.015, 0.018, 0.131), isopter area II (0.107, 0.120, 0.087), isopter area III (0.392, 0.425, 0.015) Contralateral: isopter area I (0.017, 0.021, 0.222), isopter area II (0.119, 0.125, 0.333), isopter area III (0.416, 0.434, 0.171) Conclusions: We found a statistically significant extension of the ipsilateral peripheral isopter area (III). Further studies will focus on the question which subgroup is most likely to profit from internal carotid endarterectomy with respect to visual field changes.